Antimicrobial susceptibility and genetic characterisation of oxytetracycline‐resistant Edwardsiella tarda isolated from diseased eels. (30th August 2014) - Lo, D. Y.; Lee, Y. J.; Wang, J. H.; Kuo, H. C.
Abstract : Edwardsiellosis is one of the most important bacterial diseases in eels. Edwardsiella tarda ( E. tarda ) isolates (n=94) from diseased eels were screened against the eight most commonly used antimicrobial agents in aquaculture in Taiwan. These isolates were highly susceptible to ampicillin, amoxicillin, florfenicol, oxolinic acid and flumequine. In total, 20 of the 94 (21.3 per cent) isolates tested were resistant to oxytetracycline (OTC). Among the 20 tetracycline‐resistant E. tarda isolates, tet (A) was the predominant resistance determinant and was detected in 100 per cent of the isolates, whereas 90 per cent of these isolates carried the tet (M) determinant. The efflux pump inhibitor omeprazole reduced the minimum inhibitory concentrations (MICs) of OTC for these isolates by twofold to eightfold, suggesting that an intact efflux pump, presumably encoded by tet (A), is required for high‐level tetracycline resistance. Real‐time PCR experiments showed that increased expression levels of tet (A) and tet (R) could contribute to OTC resistance. Southern blot hybridisation also confirmed that the 20 OTC‐resistant E. tarda isolates all carried the TetA determinant on a plasmid that is approximately 50 or 70 kb in size, and restriction fragment length polymorphisms (RFLP) showed that the tet (A) gene was located on an 8–10 kb Eco RI fragment in all of these plasmids. The same plasmid type and RFLP patterns were detected across different farms in the same region, but differences in their pulsed‐field gel electrophoresis (PFGE) patterns were observed. This suggests a possible role for horizontal spreading and local transmission of the plasmid in the OTC‐resistant E. tarda population of eels from two different geographic origins.